2019
DOI: 10.7554/elife.48907
|View full text |Cite
|
Sign up to set email alerts
|

Two new polymorphic structures of human full-length alpha-synuclein fibrils solved by cryo-electron microscopy

Abstract: Intracellular inclusions rich in alpha-synuclein are a hallmark of several neuropathological diseases including Parkinson’s disease (PD). Previously, we reported the structure of alpha-synuclein fibrils (residues 1–121), composed of two protofibrils that are connected via a densely-packed interface formed by residues 50–57 (Guerrero-Ferreira, eLife 218;7:e36402). We here report two new polymorphic atomic structures of alpha-synuclein fibrils termed polymorphs 2a and 2b, at 3.0 Å and 3.4 Å resolution, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
309
5
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(350 citation statements)
references
References 90 publications
32
309
5
4
Order By: Relevance
“…In addition, the packing of the central layer against the start of the outer layer in multiple recombinant α-synuclein structures, including the formation of a salt bridge between E46 and K80, is similar to that in the structures of MSA protofilaments. It has been suggested that the additional densities in front of the side chains of K43, K45 from one protofilament, and of K58 from the other, correspond to phosphate ions (61,64). Recombinant α-synuclein exhibits an increased propensity to aggregate upon exposure to anionic phospholipids (68,69).…”
Section: Recombinant Alpha-synucleinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the packing of the central layer against the start of the outer layer in multiple recombinant α-synuclein structures, including the formation of a salt bridge between E46 and K80, is similar to that in the structures of MSA protofilaments. It has been suggested that the additional densities in front of the side chains of K43, K45 from one protofilament, and of K58 from the other, correspond to phosphate ions (61,64). Recombinant α-synuclein exhibits an increased propensity to aggregate upon exposure to anionic phospholipids (68,69).…”
Section: Recombinant Alpha-synucleinmentioning
confidence: 99%
“…MSA brains with those assembled in vitro from recombinant wildtype and mutant α-synucleins(60)(61)(62)(63)(64)(65)(66)(67) [Figure 3d-f; Extended Data Figure 12]. The greatest differences are in the extended sizes of the MSA protofilaments and in their asymmetrical packing.…”
mentioning
confidence: 99%
“…Polymorphic core structures have been determined in the WT and mutant α -syn fibrils (22)(23)(24)(25)(26)(27)(28)(29)(30)(31), which are commonly composed of segment ~40-100 or smaller. Both the Cterminus and the majority of the N-terminus remain flexible, and thus are invisible in the cryo-EM structures.…”
Section: Discussionmentioning
confidence: 99%
“…One was left at 4°C; the other 6 were then shaken together. Strikingly enough, using the classical amyloid probe Thioflavin T (ThT) ( 25 ) to monitor the fibrillization ( 16,17 ), we observed a major variability in the development of the ThT signal from one tube to another (Fig. 1B).…”
mentioning
confidence: 92%
“…Strikingly, during amyloid stacking α-syn can adopt several distinct structural folds resulting in the emergence of fibril polymorphs ( 11-17 ). Together with their specific fold, their supramolecular properties also get inherited and propagated as the polymorphs self-replicate by templated growth ( 18-21 ).…”
mentioning
confidence: 99%